Development of a cost-effective, multifunctional SNP panel and analysis workflow for Wolf monitoring in Finland - Harmoinen, Jenni; Valtonen, Mia; Fischer, Daniel; Iso-Touru, Terhi; Åkesson, Mikael; Heikkinen, Anne-Maarit; Holmala, Katja; Kojola, Ilpo; Salmela, Elina; Hindrikson, Maris; Saarma, Urmas; Lohi, Hannes; et al. (Springer Nature, 2025)
Genetic monitoring is an essential tool for managing threatened or commercially valuable wildlife species. Ideally, genetic monitoring relies on straightforward protocols for genotyping and data handling, accommodates varying sample volumes, applies to non-invasive samples such as scat and hair, produces reliable and repeatable genotypes, and is cost-effective. Moreover, the marker panel itself should be tailored to specific species and/or population management information needs. We describe the development of a microarray-based 96-SNP panel specifically designed for non-invasive genetic monitoring of the Finnish wolf population. The panel was developed to meet four specific needs for this population: identification of wolf genotypes from the non-target species (fox, raccoon dog, golden jackal), sexing, individual identification, and kinship resolution. We demonstrate the utility of the SNP panel using a subset of the genetic monitoring data collected in 2022–2023, including an overview of the data analysis workflow. The development and successful application of this SNP panel, along with a comparison with similar studies in the field, provide valuable insights for researchers and conservationists aiming to implement similar strategies for other species.
Keywords: wildlife management; microfluidic array; non-invasive samples; single-nucleotide polymorphism; grey wolf; microsatellites